Pengaruh Signifikan Pada Profesional Guru Terhadap Prestasi Belajar Siswa Pada Mata Pelajaran Ekonomi Kelas VIII SMPN 2 Jerowaru - Muhamad Zaril Gapari (Al-Faiza : Journal of Islamic Education Studies, 2023)
Professional teachers are those who are qualified, competent, and teachers who desire to bring about learning achievement and can influence the teaching and learning process of students which will result in good student learning achievement. Teachers or educators are true leaders, wise guides and directors, figures, and leaders of the ummah. Teachers are professional educators with the main task of educating, teaching, guiding, directing, training, assessing, and evaluating. Teachers are professional educators with the main task of educating, teaching, guiding, directing, training, assessing, and evaluating students in primary and secondary education. as well as students in primary and secondary education. This study aims to determine the effect of professional teachers on learning achievement in economic subjects in class Kelas VIII SMPN 2 Jerowaru. The type of research used in this research is descriptive research. This study uses a quantitative approach. The population in this study were all students of class VIII SMPN 2 Jerowaru and the sample was 22 students of class VIII. The data collection technique used was a questionnaire. The data analysis technique used is the "r" test. Based on the research results, the analysis obtained shows that there is an effect of teacher professionalism on learning achievement in economic subjects in class Kelas VIII SMPN 2 Jerowaru. This can be proven from the data that has been collected that the highest score for the variable teacher professionalism (X) is 72 and the lowest score is 67, while for learning achievement (Y) the highest score is 85 and the lowest is 75. From the calculation results obtained an average (the mean) for the teacher professionalism variable (X) was 68.67 with a standard deviation (SD) of 3.3. Whereas for student achievement (Y) the average (mean) is 79.11 with a standard deviation (SD) is 2.55. whereas from the test results "rxy" or "ro" is greater than the "r" table or "r" table, both at the 5% and 1% significant levels, namely (0.711> 0.304 / 0.393). It can be concluded that: there is a significant influence on the professionalism of teachers on student achievement in Economics subject for Class VIII SMPN 2 Jerowaru.